Coupling a power system model to a building model to evaluated the flexibility potential of DSM at country level. - Quoilin, Sylvain; Georges, Emeline; Jiménez-Navarro, Juan-Pablo; Kavvadias, Konstantinos C. (Aalborg Universitet, 2017)
The integration of renewable energy sources in the electricity production mix has an important impact on the management of the electricity grid, due to their variability. In particular, to ensure grid balancing, there is a rising need for flexibility, both on the supply and demand sides. A possible solution to help achieve grid balancing is the smart modulation of the electrical load in a "demand following supply" scheme through demand-side management. In this context, the objective of this work is to assess the maximum amount of flexibility that can be harvested from the management of residential thermostatically-controlled loads (TCL) and, in particular, through the use of heat pumps, electrical heaters and thermal storage. To that end, a modelling framework is developed to couple a power system model (in this case the open-source Dispa-SET v2.2 model) with the model of a set of building typologies using heat pumps or electrical heaters for space heating and/or domestic hot water production.
En acceso abierto en la web original.
Keywords: Bombas de calor; Calor - Almacenamiento; Flexibility; DSM; Heat pump; Power dispatch; Thermal storage